Gamma-Ray Shielding Effectiveness of Clay and Boron Doped Clay Material at Different Thicknesses - Sameer, Ahmed Salih; Ali , Akram Mohammed (Iraqi Journal of Science, 2022)
In this work, the gamma-ray shielding parameters of red clay and boron-doped red clay with different sample thicknesses are theoretically and experimentally reported. These shielding parameters are considered at a photon energy of 0.662 MeV emitted from 137Cs. The theoretical calculations are demonstrated using the XCom software program, while a scintillation detector, NaI(TI), with an efficiency of 98% is used to attain the experimental results of the mass attenuation coefficient of the prepared samples. The acquired results show that the boron-doped clay delivers a higher mass attenuation coefficient as compared to those of pure clay. Additionally, the mass attenuation coefficient exhibits an increasing behavior with the sample thickness increment.